Attitude of Coastal Rural Youths Towards Some Selected Modern Livestock Technologies - Rashid, MU; Uddin, ME (The Agriculturists, 2010)
A study was conducted to determine the attitude of the coastal rural youth towards some selected modern livestock technologies. Data were collected from randomly selected 91 youths of Patuakhali district using a structured interview schedule during 15 May to 31 May 2007. Coastal rural youths attitude towards some selected livestock technologies was the dependent variable of the study. Ten selected individual characteristics of the respondents namely, age, education, family size, family farm size, family annual income, aspiration, innovativeness, extension media contact, agricultural knowledge and time spent in agricultural activities were considered as the independent variables of the study. Majority of the coastal rural youth (49.4 percent) had moderately favourable attitude, while 28.6 per cent had less favourable and 22 per cent had highly favourable attitude to modern livestock technologies. Among the ten selected independent variables aspiration, extension medial contact and agricultural knowledge had positive significant relationship with coastal youths attitude towards some selected livestock technologies.